A Review of the Influence of Music on Foreign Language Teaching (1998-2024) - Li, Zhanpeng; Liu, Shuo (International Theory and Practice in Humanities and Social Sciences, 2025)
With the continuous progress of contemporary science and technology and cognitive neuroscience, a series of studies have revealed the significant overlap between music and language in the brain processing area, which provides important theoretical support for the transfer of music as an interdisciplinary tool to the field of foreign language teaching and research. Therefore, in-depth study of the interaction between music and language has a positive role in promoting the optimization of foreign language teaching strategies. Based on the review of 65 relevant studies (1998-2024) , this article aims to explore the potential role of music in foreign language learning and make an in-depth analysis of the limitations of the current research, providing beneficial suggestions for future foreign language teaching and theoretical research.